A lingua franca for the Internet. (Economist, 2001)
Part of a special section on technological innovation. Far from promoting one universal programming language, the Internet is encouraging a multiplicity of new ones. The dispute between Sun Microsystems, producers of Java, and Microsoft, creators of C#, is being followed with great interest by both the financial world and as programmers. Java has become synonymous with programming for the Internet, and the language played a key role in the protracted legal battle between Microsoft and the U.S. government's trust-busters. It was therefore not surprising that Microsoft launched its own programming language in 2000. However, things are changing within the world of programming semantics. When the time is right, a new language that incorporates concepts from artificial intelligence will emerge that will leave Java and C# behind. The evolution of programming languages and how these languages face the daunting task of helping to turn the Internet into a more intelligent place are discussed.